STUDY OF THE RELATIONSHIP BETWEEN LEARNING MOTIVATION AND STUDENT ACHIEVEMENT - Muhammad Awin Alaby; Mardiana Sari; Sri Lela (CV. Bunda Ratu, 2023)
Learning is an activity that involves teachers and students. Teaching behavior and learning process are influenced by students' learning motivation. The existence of student learning motivation will provide enthusiasm and learning becomes more focused for students. Building intrinsic motivation in students will be better than extrinsic motivation. By intrinsically motivating students to learn because of their sincerity, positive results of learning efforts are shown. However, extrinsic motivation also determines students' interest in learning. When students have a desire to learn but extrinsic factors are not supportive, students will lose their enthusiasm. Both intrinsic and extrinsic factors can determine student success in the learning process. Motivation is the energy of change within a person characterized by effective arousal and anticipatory goal reactions. Motivation will encourage, move and direct students to learn. Students who have high learning motivation will carry out activities in acquiring knowledge. Motivation will arouse students' interest in learning.